The axial and lateral behavior of low strength concrete confined by GFRP wraps: An experimental investigation. (October 2020) - Khaloo, Alireza; Tabatabaeian, Mojtaba; Khaloo, Hooman
Abstract: The purpose of this investigation is to investigate the axial and lateral behavior of low strength concrete confined by glass fiber reinforced polymer (GFRP) wraps. A total of 48 cylindrical samples having 150 mm diameter and 300 mm height were strengthened and examined. The mix designs were provided with four different target strength (5, 10, 15, and 20 MPa). The axial and lateral strain were studied to evaluate the axial strain relation and the lateral strain for axial compression. The results of this investigation present a comparison between the nine models previously reported for normal strength concrete and the lesser-known context of low strength concrete confined by fiber reinforced polymer (FRP) composites. The results obtained from this study show that the majority of models reported for normal strength concrete, can accurately predict the stress improvement ratio for low strength concrete (LSC), however, one of the models exactly predicts the strain improvement ratio for all ranges of LSC. The results also show that an increase in compressive strength of concrete causes a decrease in both stress improvement ratio and strain improvement ratio. The analysis of variance (ANOVA) was applied to study the percentage effect of the key criteria to the stress improvement ratio, strain improvement ratio, and the strain factor of LSC, where the results reveal that the compressive strength is a more effective criterion on the stress and strain improvement ratios and the strain factor than the confinement level (number of GFRP layers). Finally, lateral strain-axial strain behavior of GFRP and actively confined concrete is compared and it is understood that lateral strain- axial strain behavior of confined specimens is affected by lateral pressure and unconfined concrete strength.